Surgical Treatment of Atrial Fibrillation with Electhocautery during Mitral Valve Replacement - Sarker, Rampada; Sarker, Manoz Kumar; Ali, Md Ataher; Beg, Abdul Khaleleque (Cardiovascular Journal, 2016)
Background: The Maze procedure is the surgical treatment that can alleviate the three complications of atrial fibrillation- tachycardia, thrombo-embolism and hemodynamic compromise. We attempted ablation of atrial fibrillation with monopolar eletrocautery.Our objective was to evaluate the results of surgical treatment of atrial fibrillation by ablation of the left atrial wallaround the pulmonary veins with conventional electrocautery during mitral valve replacement. Methods:This retrospective observational study was carried out in the Department of Cardiac Surgery, National Institute of cardiovascular diseases, Dhaka, Bangladesh,from January 2014 to February 2016. Ablation of AF with monopolar electrocautery was done during mitral valve replacement. Recurrence of atrial fibrillation, any new arrhythmia, complete heart block, bleeding and perforation was noted during the operation and in postoperative period. Patients were followed up upto three months after the surgery. Results: All the Patients were free from atrial fibrillation after the procedure. At discharge 100 %, after I month 96.2% and after 3 months 92.3 % patient were free from atrial fibrillation. No patients developed complete heart block requiring pace maker and there was no incidence of atrial perforation at the sites of ablation. Conclusion: The surgical treatment of the atrial fibrillation with elcetrocautery during mitral valve replacement is able to reverse this arrhythmia in a significant number of patients during short term follow-up without any complication. Cardiovasc. j. 2016; 9(1): 9-12